Pesquisas sôbre a análise estatística de experiências de adubação com o auxílio da lei de Mitscherlich - Gomes, Frederico Pimentel; Malavolta, Eurípedes (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1950)
Statistical analyses of an experiment on wheat were carried out with the aid of Mitscherlich's law. The experiment was made in Ponta Grossa, Paraná, by the Ministry of Agriculture of Brasil. Lime, in the form of Ca(OH)2, was applied at the levels of 0, 2, 4, 6 and 8 metric tons per hectare. A 5 x 5 Latin square was used. Lime was applied in 1940 and wheat was cultivated in the same plots for several years. The following fertilizers were annually used for all plots: NaNO3 100 kilograms per hectare, Superphosphate 350 kilograms per hectare, K2S04 80 kilograms per hectare. The statistical analysis of the data collected in 1941, 1942, 1943, 1947 and 1948, carried out in accordance with the methods previously introduced by Pimentel Gomes and Malavolta (1949 a, 1949 b) and Pimentel Gomes (1950), proved: I. That Mitscherlich's law could be correctly applied to the data. II. That there was a statistically significant effect of lime on wheat yield. III. That the optimum amount of lime to be applied to the soil lies between 5 and 15 hundred kilograms of Ca(OH)2 per hectare. IV. That there is a migration of calcium from some plots to others, in such a way that the data obtained in 1947 and 1948 are not representative of the amounts of lime applied in 1940. V. That the analysis of variance can be used, as the Bartlett test shows that the variances at the distinct levele of lime application are not statistically different. It must be noted that, with improved variety and fertilization, the yield was rised to about 2500 kilograms per hectare in 1947, and 1600 in 1948, being only of about 100 kilograms per hectare in 1940.